Heavy metals in sediments and fishery catches from the Beibu Gulf, China: Bioaccumulation, potential risks, and human - Zhao Shuwen; Huang Liangliang; Wang Caiguang; Yang Yiheng; Yang Xi (E3S Web of Conferences)
In this study, 3 species of fishey catches (Pennahia macrocephalus, Saurida tumbil, and Upeneus sulphureus) and sediments were collected from the Beibu Gulf to identify the residual levels, human health risk, and ecological risk of HMs (As, Cd, Cr, Cu, Hg, Mn, Ni, Pb, and Zn). The average concentrations (dry weight) of As, Cd, Cr, Cu, Mn, Ni, Pb, and Zn in the three species of fish were recorded as follows: 10.94, 0.11, 0.55, 2.00, 5.80, 0.47, 0.39, and 41.70 mg/kg, respectively. The health risk assessment results indicated that adults who consume these organisms could encounter carcinogenic health hazards, while children consuming these species may experience notable negative health effects. The contents of studied HMs reached China’s national first-class benchmark of marine sediment quality. The ecological risk index (RI) of HMs from surface sediments ranged from 17.77 to 133.88, with a mean value of 56.45, which portrayed minor potential.